880 Electrophysiological Patterns of Glioma-Induced Neuronal Network Remodeling are a General Property of Brain Tumors Regardless of Subtype. (April 2023) - Aabedi, Alexander Arash; Lipkin, Benjamin; Young, Jacob; Hinkley, Leighton; Findlay, Anne; Daniel, Andy; Krishna, Saritha; Umbach, Gray; Surapaneni, Akhil; Kaur, Jasleen; Berger, Mitchel; Molinaro, Annette; et al.
Abstract : INTRODUCTION: Recent evidence indicates that diffuse gliomas engage with neurons at the single-unit and circuit level through differing mechanisms. Certain malignant gliomas form glioma-neuron excitatory glutamatergic synapses and modulate neuron-neuron synapses through activity-dependent paracrine signaling, while others establish glioma-glioma connections via tumor microtubes. It is therefore possible that diffuse gliomas remodel neuronal circuits in a defined and predictable manner and demonstrate distinct electrophysiological profiles with prognostic and therapeutic significance. METHODS: Following spatial-temporal registration, an elastic net logistic regression classifier was used to distinguish between power spectra arising from glioma-remodeled cortex and within-subject control conditions (N = 140). Model significance was determined non-parametrically by re-training each model 1, 000 times with randomly permuted class labels and testing the true phi coefficient against the null distribution. RESULTS: In the discovery dataset, glioma infiltration was accurately classified based on tumor intrinsic neuronal activity (p < 0.05) in 127 patients (90.7%). Thirty electrophysiological features were identified, which revealed increased power in the delta range (1-4 Hz) and decreased power in the beta range (12-20 Hz) as a unique signature of glioma remodeling (p < 0.05) which was preserved in the validation dataset as well as across WHO 2021 diffuse glioma subtypes. To identify gene expression programs and signaling mechanisms that may contribute to glioma-induced remodeling but are potentially not identified in the current clinical classification scheme, targeted, next generation sequencing was performed and used as covariates, which again demonstrated the significance of the delta-beta spectral features. CONCLUSIONS: These data support converging mechanisms of glioma-induced neuronal network remodeling across tumor subtypes, setting the stage for novel therapies such as neuromodulation.